Response surface method in the optimization of a rotary pan-equipped process for increased efficiency of slow-release coated urea - Babadi, Farahnaz Eghbali; Yunus, Robiah; Abbasi, Ali; Soltani, Salman Masoudi (MDPI, 2019)
The high solubility of urea in water and its consequent leaching into the soil adversely prevents its full assimilation by plants. An improved slow-release process could effectively minimise the loss of fertilizer material and thus mitigate the associated environmental pollution. In this study, the effects of the operational variables on the efficiency of the urea coating process in a rotary pan have been systematically analysed. A mixture of gypsum-sulphur was used as the coating material with refined water as a binder. In order to comprehensively investigate the impact of each process variable on the efficiency and any potential interactions between them, the effects of particle size, coating material percentage, rotational speed of the pan, spray flow rate and the amount of sprayed water were investigated and analysed via a central composite design of experiments (DoE). The second-order polynomial model provided the best correlation for the experimental data. The predictive model was then used to estimate the efficiency of the coated urea as a function of the statistically-significant variables. The results revealed an increase in the efficiency of the coated urea from 22% to 35% (i.e., ~59%) when prepared under the optimum process conditions.